Time, cycles and ritual behaviour - Morley, I (Oxbow Books, 2010)
This paper attempts to touch upon a number of issues attendant upon considering the nature, purposes and motivations for ritual activity; there is not the space to do more than scratch the surface of either the relevant literature or the implications of the considerations here, but it is hoped that there is enough to form a starting point for further thought and investigation.